2017
DOI: 10.1136/bmjopen-2017-017183
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sector user and provider perceptions on experiences of shared-care clozapine: a qualitative study

Abstract: Objectives(1) To explore individual perceptions on experiences of people receiving and/or delivering a shared-care clozapine serviceand (2) to gain an understanding of effectiveness and acceptability of shared-care clozapine.DesignInterpretative phenomenological analysis guided the delivery and analysis of a semistructured interview and focus group study designed to explore participant experience of shared-care clozapine. Ethical approval 13/EM/0286 was gained in July 2013 from East Midlands—Nottingham 1 REC.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…To our knowledge, little research on such programs has been undertaken in an Australian context, but at least one study has shown successful outcomes from a clozapine shared care program, with almost no re‐hospitalisations in the year following transfer to the program 14 . Also, studies conducted in Australia and the United Kingdom have shown high degrees of satisfaction with clozapine shared care among patients and health care workers 11,16 . The program that we have described is successful due to the clear delineation of roles and responsibilities, contingency planning, and mutual partnerships between primary and secondary care, with all parties having access to the service’s clozapine policy (which outlines the program in detail).…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, little research on such programs has been undertaken in an Australian context, but at least one study has shown successful outcomes from a clozapine shared care program, with almost no re‐hospitalisations in the year following transfer to the program 14 . Also, studies conducted in Australia and the United Kingdom have shown high degrees of satisfaction with clozapine shared care among patients and health care workers 11,16 . The program that we have described is successful due to the clear delineation of roles and responsibilities, contingency planning, and mutual partnerships between primary and secondary care, with all parties having access to the service’s clozapine policy (which outlines the program in detail).…”
Section: Discussionmentioning
confidence: 92%
“…This mirrors the findings of a previous evaluation of community shared-care clozapine monitoring, where forensic healthcare professionals were motivated by enabling patients to develop skills for independence. 7 Both staff and patients believed that physical and mental healthcare were equally important for people taking clozapine. 7 In our study, there was a range of understanding among patients, with stepdown patients having greater understanding of the associated benefits of monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…7 Both staff and patients believed that physical and mental healthcare were equally important for people taking clozapine. 7 In our study, there was a range of understanding among patients, with stepdown patients having greater understanding of the associated benefits of monitoring. Their engagement is a further key facilitator to be harnessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations